Geospatial-Based Decision Framework For Mitigating Potential Soil Degradation Risks in Sustainable Agriculture Halong, South Kalimantan - Romadhon, Muhammad Rizky; Georges, Suman; Hadi, Abdul; Sakti, Muchammad Bima Gegana; Fauzan, Adhia Azhar; Septiana, Meldia; Ratna, Ratna; Utami, Aditya Dyah; Auliyya, Zikra; Puspitaningrum, Ismi Nuari (Universitas Sebelas Maret, 2026)
Soil degradation is a major constraint to agricultural sustainability, particularly in areas characterised by diverse environmental conditions. Halong District, Balangan Regency, South Kalimantan Province, is characterised by heterogeneous land uses, soil types, slope variations, and variable rainfall patterns, which influence soil quality and degradation risks. This research aims to assess the potential for soil degradation concerning environmental diversity and its implications for sustainable integrated agriculture. The study highlights that differences in land use, from shifting cultivation to permanent farming, combined with acidic soils, steep slopes, and uneven rainfall distribution, increase vulnerability to erosion, nutrient depletion, and declining soil fertility. The results show that the Potential Soil Degradation Risk (PSDR) in the low-risk class (PSDR.II) covers 298.22 km2 (45.20%), followed by the intermediate-risk (PSDR.III) covering 335.15 km2 (50.79%), and the high-risk (PSDR.IV) covering 26.48 km2 (4.01%). Land use and slope are determining factors for PSDR, as indicated by ANOVA, DMRT, and correlation test results. Understanding these linkages is essential for designing site-specific land management practices that reduce degradation risks while improving agricultural productivity. The outcomes of this research are expected to provide scientific recommendations for stakeholders in developing sustainable agricultural management strategies, such as soil conservation, organic matter management, and integrated crop-livestock systems, to mitigate degradation risks and support long-term agricultural resilience in Halong District.